Baby food industry interference with infant feeding international regulation—A case study on the standard for follow-up formula - Silva, Kimielle Cristina; Castro, Inês Rugani Ribeiro de; Carvalho, Camila Maranha Paes de; Camargo, Kenneth Rochel de (Frontiers in Public Health, 2022)
Increased growth of commercial breast milk substitutes (BMS) consumption, including follow-up formulas and toddler formulas, have resulted in changes to first-food systems and discontinuation of breastfeeding around the globe. The products are manufactured by a small number of corporations leader BMS sales around the globe. Discussions about these products global regulatory compliance are held on Codex Alimentarius scope and are marked by a strong participation of these corporations at their boards. The study reviewed baby food industry role in Standard for Follow-up Formula regulatory process in accordance with Codex Committee on Nutrition and Foods for Special Dietary Uses (CCNFSDU) requirements. The analysis of the documents of the CCNFSDU referring to the period from 1966 to 2019 used quantitative and qualitative approaches. Compositional and participation data from country delegations and observer organizations were systematically established, as well as these institutions representatives profile and the baby food industry involvement in this process. Of the 189 Codex Alimentarius member countries, 134 countries engaged in the Standard review process and, of these, 28% of the countries were involved in the entire process. Private sector represented 81% of the delegations that more regularly attended the meetings. For observer organizations involved in the review process, approximately 60% of the organizations were business associations representing industry interests. The International Special Dietary Foods Industries (ISDI) was the only observer organization advocating for baby food industry interests in the review process. This research results suggest that the Codex Alimentarius main goal of protecting consumers' health may not be reached. Standard for Follow-up Formula review counted with these industries participation, both in Member States delegations and in observer organizations composition. Few studies elucidate Codex and its respective committees’ public documents, and this was the first to carry out an analysis of baby food industry influence on BMS global regulatory compliance.